Phylogeography and evolutionary genetics of the weasel : (Mustela Nivalis) - Rodrigues, Mónica (2016)
Tese de doutoramento, Biologia (Biologia Evolutiva), Universidade de Lisboa, Faculdade de Ciências, 2015